1971
DOI: 10.1017/s0003356100029810
|View full text |Cite
|
Sign up to set email alerts
|

A note on the relationship between the rate of machine-milking and milk production of Ayrshire heifers

Abstract: SUMMARYRecords of milking rate, milk yield and milk composition were collected over 12 yr from 123 Ayrshire heifers in their first lactation in one herd. Three direct measures of milking rate, i.e. peak flow rate, machine rate and overall rate were closely correlated and each was also correlated with total lactation yield of milk. Milking rate accounted for only a very small part of the variation in fat and total solids percentages. The mean yield of milk per milking in early lactation was a better predictor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Among animals giving the same early lactation yield of milk, the faster milkers gave higher lactation yield than the slower milkers (Castle and Henderson, 1971). Using two groups that were purchased on pedigree esimtates of breeding value for milk yield, Chyr et al (1974) found that pedigree high cows had higher peak flow rate (9.7 vs. 8.4 Ib/min), and more yield in the first minute (9.0 vs. 7.9 Ib/min).…”
Section: Sandvikmentioning
confidence: 97%
See 1 more Smart Citation
“…Among animals giving the same early lactation yield of milk, the faster milkers gave higher lactation yield than the slower milkers (Castle and Henderson, 1971). Using two groups that were purchased on pedigree esimtates of breeding value for milk yield, Chyr et al (1974) found that pedigree high cows had higher peak flow rate (9.7 vs. 8.4 Ib/min), and more yield in the first minute (9.0 vs. 7.9 Ib/min).…”
Section: Sandvikmentioning
confidence: 97%
“…A controversy exists as to the relationship between rate of milking and the total lactation yield. Brumby (1961) demonstrated no genetic correlation between lactation yield and peak flow rate, while other researchers have found rate of milking to be related to lactation yield (Castle and Henderson, 1971;Clough and Dodd, 1957;Dodd and Neave, 1951;Donald, 1960;Johansson and Malven, 1961;Kawanishi et al, 1982;Miller et al, 1976;Rajamannan et al, 1966;Tomaszewski and Legates, 1972). Donald (1960) found that 11% of the variation in yield was removed by holding peak rate constant and concluded that high producing cows tended to be rapid milkers.…”
Section: Milk Flow and Lactation Yieldmentioning
confidence: 98%